Analysis of the Capital Structure and Profitability of Manufacturing Companies Listed on the Ghana Stock Exchange - Aidoo, Emmanuel; Ahmed, Ibrahim Anyass; Musah, Alhassa (Asian Journal of Economic Modelling, 2022)
Manufacturing companies play a crucial role in the economies of most developing countries. Decisions on capital structure portend great importance for businesses vis-à-vis the daunting task of coping with competition within the business landscape. This makes capital structure decisions a reality rather than a myth. Coupled with the daily activities of manufacturing businesses, profitability ensures economic growth and increases in taxes. Profitability is also influenced by the ideal combination of debt and equity. Using descriptive and causal research designs, this study assesses the impact of capital structure on profitability for the period from 2005 to 2019 of listed manufacturing companies in Ghana. Results indicate a significant correlation between capital structure and profitability. The independent variables are found to be inversely related to profitability. Based on these findings, companies may need to minimize the debt component of their capital structure in order to increase profitability.